The Seventeenth-Century Resolve : A Historical Anthology of a Literary Form - Lievsay, John Leon (Book collections on Project MUSE., 2015)
Popular in its time, the resolve is now almost forgotten. In this anthology John L. Lievsay has gathered a representative collection of resolves and has provided also a critical history of the genre -- its flowering and decline.